Eficiência de genótipos de soja no uso do fósforo - Alves, Veranice Silviane Borges (2018)
The development of efficient cultivars in the use of phosphorus (P) is the alternative to reduce costs with phosphate fertilization in tropical regions. The objective of this work was to characterize soybean genotypes regarding phosphorus efficiency for the selection of parents. The experiment was conducted in the field between December 2016 and April 2017. The factors studied were eight soybean genotypes (UFUS 8710, UFUS Xavante, UFUS Milionária, UFUS 7910, UFUS 8301, UFUS 6901, UFUS 7415 and UFUS 7401) and 4 doses of P (30, 60, 90 and 120 kg ha-1 of P2O5). The following characteristics were evaluated: plant height at flowering (APF) and maturity (APM); number of nodes in flowering (NNF) and maturity (NNM); SPAD index; (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S); phosphorus absorption efficiency (EAP); efficiency in the internal use of phosphorus (EUtP) and efficiency in the use of phosphorus (EUP). The data were submitted to analysis of variance and then the grouping of means by the Scott Knott test. The generalized distance of Mahalanobis was estimated between pairs of genotypes, and then the dendrogram was obtained by UPGMA method and by Tocher. The analyzes revealed the existence of genetic variability among the genotypes for almost all analyzed variables. The genotype UFUS 6901 is efficient in the absorption and the use of phosphorus, while UFUS 8710 is efficient in the internal use of this nutrient. The greatest dissimilarities were verified between these genotypes and between UFUS 6901 and UFUS Millionaire, therefore, these are potentials for hybridizations aimed at efficiency in P in terms of plant development, being the hybridizations UFUS 6901 x UFUS Milionária and UFUS 6901 x UFUS 8710 the most recommended. The dose of P corresponding to 50% of that recommended for soils of very low availability of this element is the most favorable for the selection of efficient parents, as it revealed the maximum genetic dissimilarity among the genotypes.